Global epidemiology of acute generalised peritonitis: a protocol for a systematic review and meta-analysis - Celestin Danwang; Joel Noutakdie Tochie; Aime Mbonda; Ndip Valirie Agbor; Tianyi Tianyi Frank Leonel; Desmond Aji Abang (BMJ Open)
Introduction Globally, acute generalised peritonitis (AGP) is a common medical and surgical emergency which is a major contributor to non-trauma deaths despite improvements in diagnosis and surgical and intensive care management. In order to determine the global burden of AGP, geared at tailoring key interventions to curb its morbidity and mortality, we proposed this first ever systematic review and meta-analysis to estimate the contemporary prevalence, and to determine the most frequent AGP and the case fatality rate of AGP, at the global scene.Methods and analysis We intend to search AfricanJournalsOnline, Americana em Ciências da Saúde, Citation index, EMBASE, Global Index Medicus, Literatura Latino Africa Index Medicus, Medline and Scientific Electronic Library Online databases from 1 January 2009 to 31 July 2019 to identify studies that reported the prevalence, types of AGP, and case fatality rate of AGP in the global population without any language restrictions. Study selection, data extraction and risk of bias assessment will be conducted independently at each level by a pair of independent investigators. Random-effects meta-analysis will be used to pool studies judged to be clinically homogeneous. The presence of heterogeneity will be evaluated using the χ² test on Cochrane’s Q statistic and quantified with the I² statistics. Publication bias will be evaluated statistically and visually using the Egger’s test and funnel plots, respectively. Findings will be reported and compared by countries, WHO regions and globally.Ethics and dissemination Since this study will be based on published data, it does will not require an ethical approval. The findings will be published in a scientific peer-reviewed journal. They will also be presented at scientific conferences and to relevant public health actors.PROSPERO registration number CRD42019143331.